The miracle of life - Dale, Richard; Goldberg, Robert (Wonders of the human body, 2002)
In this programme you will see cells dividing, an embryo developing, a baby in the womb about to be born. Marvel at the miracle of genetics, all the information rquired to create arteries, organs, mind, memory, and personality are contained in the single original cell. Through state of the art imaging techniques, miniscule inside the body cameras, time-lapse photography, computer morphing, digital animation and more the whole family can see, understand and enjoy the science of this astonishing creation of human body.